Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1097/00003246-200103000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Improved survival in cancer patients requiring mechanical ventilatory support: Impact of noninvasive mechanical ventilatory support

Abstract: Our results confirm that mortality has improved over the past decade in critically ill cancer patients, even those who require MV, and suggest that this may be, in part, because of a protective effect of NIMV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

19
193
7
23

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 347 publications
(242 citation statements)
references
References 35 publications
19
193
7
23
Order By: Relevance
“…The total number of haematology admissions to hospital during the time period (2006)(2007)(2008) are not known, so it is possible that the absolute increase in level 3 ICU admissions reflects an absolute increase in hospital admissions, and that the use of critical care outreach teams masks the increase in level 2 requirement. The study confirmed the findings of other studies that good outcomes in terms of short-term and medium-term survival are possible in this cohort of patients with 53% of patients discharged from ICU back to the ward, and in 33% of patients being alive at 6 months, out of which, majority (91%) were in complete remission from their respective haematological conditions [10][11][12]. We also looked at the outcomes of all non-surgical patients admitted to ICU as well as hospital mortality for comparison with patients with haematological malignancies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The total number of haematology admissions to hospital during the time period (2006)(2007)(2008) are not known, so it is possible that the absolute increase in level 3 ICU admissions reflects an absolute increase in hospital admissions, and that the use of critical care outreach teams masks the increase in level 2 requirement. The study confirmed the findings of other studies that good outcomes in terms of short-term and medium-term survival are possible in this cohort of patients with 53% of patients discharged from ICU back to the ward, and in 33% of patients being alive at 6 months, out of which, majority (91%) were in complete remission from their respective haematological conditions [10][11][12]. We also looked at the outcomes of all non-surgical patients admitted to ICU as well as hospital mortality for comparison with patients with haematological malignancies.…”
Section: Discussionsupporting
confidence: 90%
“…This is reflected in the increasing proportion of patients surviving after mechanical ventilation and conflicts with previous studies which indicate mechanical ventilation to be a marker of poor outcome [12,[16][17][18][19]. Failure of greater than two organs, neutropenia, renal support and inotropic support were significant factors on univariate analysis, but on multivariate analysis, only failure of greater than two organs proved to be an independently significant factor adversely affecting survival.…”
Section: Discussionmentioning
confidence: 67%
“…Similarly, the outcome of cancer patients admitted to the ICU with severe sepsis or septic shock [6], acute respiratory distress syndrome (ARDS) [8], or those requiring mechanical ventilation [12] has also improved steadily in recent years. When examined over time, these studies have reported a significant reduction in the absolute risk of hospital mortality ranging from 15 to 50 % between the early/mid-1990s and the past decade (Fig.…”
mentioning
confidence: 99%
“…Even though major advances have been achieved in the care of the critically ill hematological patient over the last 2 decades, acute respiratory failure requiring intubation and mechanical ventilation still has an associated mortality of 50-70% [1][2][3][4][5]. As such, strategies aiming to avoid intubation may have more potential to positively impact survival here than further improvements or refinements of the care of the invasively ventilated patient.…”
mentioning
confidence: 99%
“…Two small interventional trials [6,7] randomizing immunocompromized patients (including hematological patients in one study [7]) with hypoxemia and diffuse pulmonary infiltrates between therapy with NIV and supportive oxygen only found reduced rates of intubation and better survival in the NIV-treated arm, and thus founded the main scientific rationale for the use of NIV in hematological patients with ARF. Observational studies provided more conflicting results, as some of these found an association between better survival and the use of NIV as compared with invasive ventilation [2], while others identified no such protective effect of NIV [4,5]. While these observational data could not prove a beneficial effect of NIV (or a lack thereof), they provided additional insights into the relationships among the ventilator mode used, the etiology underlying ARF, and the patient outcome, which are more complex in hematological patients than for instance in COPD patients.…”
mentioning
confidence: 99%